2019
DOI: 10.12659/msm.920319
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane and Ubiquitin-Like Domain Containing 1 Protein (TMUB1) Negatively Regulates Hepatocellular Carcinoma Proliferation via Regulating Signal Transducer and Activator of Transcription 1 (STAT1)

Abstract: Background: Hepatocellular carcinoma (HCC) is a common malignancy, but the pathogenesis of HCC is unclear. TMUB1 has an inhibitory effect on normal hepatocytes, but its role in HCC has not been reported. Material/Methods: We used immunohistochemistry to observe the expression of transmembrane and ubiquitin-like domain containing 1 protein (TMUB1) and signal transducer and activator of transcription 1 (STAT1) in 132 HCC tissue specimens. The expression of TMUB1, STAT1, and CCND1 in HCC cells were detected by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…However, TMUB1 was demonstrated to be negatively correlated with HCC pathological malignancy [ 10 ] as low expression of TMUB1 correlated with poor prognosis in patients with HCC. This discrepancy may be attributed to TMUB1 playing different roles in different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, TMUB1 was demonstrated to be negatively correlated with HCC pathological malignancy [ 10 ] as low expression of TMUB1 correlated with poor prognosis in patients with HCC. This discrepancy may be attributed to TMUB1 playing different roles in different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during liver regeneration, HOPS inhibits STAT3 pathways, negatively controlling hepatocyte proliferation [8]. HOPS negatively correlates with hepatocellular carcinoma malignancy, inhibiting proliferation via STAT1 signaling and promoting ubiquitination of ∆Np63 [9]. Analyzing HOPS' role in hepatocellular carcinoma proliferation, it has been shown that tumor cell growth is suppressed by controlling the ubiquitination and degradation of ∆Np63 isoforms, thus driving cells to apoptosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of SCF/c-kit axis triggers cascade of MAPK pathways [ 21 ], of which the ERK pathway is generally responsible for cell differentiation and proliferation, whereas the JNK pathway is involved in apoptosis [ 22 ]. Additionally, the phospho-ERK translocation from the cytoplasm to the nucleus stimulates the activity of transcription factors such as STAT1/3, Pax6, and CREB [ 23 25 ]. In addition, CBP expression is markedly increased in breast cancer cells treated with cancer-associated adipose tissue [ 8 ].…”
Section: Discussionmentioning
confidence: 99%